2008
DOI: 10.1097/01.anes.0000299428.55062.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aprotinin Dosage on Renal Function

Abstract: In the current analysis, aprotinin dosage was not associated with increased adverse renal outcome. In regard to renal outcome, this analysis did not demonstrate an essential detrimental influence of aprotinin dosage on renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Dietrich, in a study of 8,548 cardiac surgical patients treated with different doses of aprotinin, showed no association of aprotinin dosage and postoperative hemodialysis or renal dysfunction. 5 The null hypothesis for this study is there is no difference in the incidence of renal failure and mortality between the use of different antifibrinolytic agents and the control group (off-pump) in coronary artery bypass patients. The primary outcomes of renal failure and mortality were compared to the results published in the larger observational study by Mangano.…”
Section: Introductionmentioning
confidence: 93%
“…Dietrich, in a study of 8,548 cardiac surgical patients treated with different doses of aprotinin, showed no association of aprotinin dosage and postoperative hemodialysis or renal dysfunction. 5 The null hypothesis for this study is there is no difference in the incidence of renal failure and mortality between the use of different antifibrinolytic agents and the control group (off-pump) in coronary artery bypass patients. The primary outcomes of renal failure and mortality were compared to the results published in the larger observational study by Mangano.…”
Section: Introductionmentioning
confidence: 93%
“…An analysis of 8548 patients published in 2008 found a lack of a dose-response relationship between aprotinin and renal failure [19], which can be explained by varying levels of glyphosate contamination in the administered drug. In 2008, Fergusson et al [20] compared aprotinin with another antifibrinolytic agent, aminocaproic acid, and found a greater than 50% relative increase for death within the first month linked to aprotinin.…”
Section: Introductionmentioning
confidence: 99%